Rethinking scenario building for sustainable futures: mobilizing conscientização, social learning and knowledge co-production - Danilo Borja; Jan Daněk; Julia C. Assis; Antonella Gorosábel; Carolyn Lundquist; Isabel Rosa; Fabio Rubio Scarano; Nino Tavares Amazonas; Silas C. Principe; Rob Alkemade; Adnan Arshad; Sandra Benavides-Gordillo; et al. (Ecosystems and People)
Scenario building is a powerful tool for evaluating drivers of environmental change and assessing alternative socioecological pathways, helping integrate science-based information into decision-making. Nonetheless, this potential has not been fully embraced by scientists and decision-makers, in part owing to limitations of current scenario frameworks at representing the diversity of values for nature and potential transformative changes to bend the biodiversity loss curve. There is still a need to further develop scientists’ capacities to include a transdisciplinary perspective in scenario building to address the drivers of transformative change. This paper addressesthese needs by reflecting on the role of scientists engaged in scenario building in the construction of sustainable futures through the lens of three key concepts: social learning, knowledge co-production and conscientização (a Portuguese term meaning to build sociopolitical awareness and take action). Drawing on a survey of participants of a Scenario Building School and a literature review, we suggest that scientists require capacity building to leverage these concepts together for the construction of transformative futures. This includes addressing power imbalances, improving inclusive and transdisciplinary participatory methods, reaching consensus and promoting action. We recommend that scientists engaged in scenario building focus on fostering transformative changes, challenging mainstream storylines, embracing diversity and addressing inequalities to pursue sustainable futures.